Faktor Yang Berhubungan Dengan Kejadian Stunting Usia 24-59 Bulan Di Wilayah Kerja Puskesmas Maiwa (Window of Public Health Journal, 2025)
Stunting, or short stature, is a nutritional status based on the height-for-age (W/A) index with a z-score of less than -2 SD (Standard Deviation). Stunting is not only a problem of impaired physical growth but also makes children susceptible to illness. In addition, brain development and intelligence are also impaired. Therefore, stunting is a major threat to the quality of human resources in Indonesia. This study aims to determine the factors associated with the incidence of stunting in children aged 24-59 months at the Maiwa District Health Center, Enrekang Regency. The study is an analytical observational study with a quantitative approach using a cross-sectional study. The population in this study was toddlers aged 24-59 months. The sampling technique used was purposive sampling. The data analysis method used was bivariate analysis with the chi-square test. The results of this study obtained maternal knowledge, maternal MUAC (mid-upper arm circumference) during pregnancy, LBW, birth length did not have a significant relationship with the incidence of stunting where ρ = 0.072, ρ = 0.093, ρ = 0.082, ρ = 0.119 means ρ> 0.05, and a history of infectious diseases had a significant relationship with the incidence of stunting where ρ = 0.024 means ρ